Barriers to the Implementation of Evidence-Based Practice in A Tertiary Care Hospital Mirpur, Azad Kashmir, Pakistan: A Cross-Sectional Study: Evidence-Based Practice Barriers in Azad Kashmir - Noreen, Safia; Fatima, Fozia; Ejaz, Kashmala; Khatoon, Zubaida; Kousar, Tanveer; Tariq, Rubab (Pakistan Journal of Health Sciences, 2025)
An approach to providing care to patients is based on problem-solving decisions on the greatest reliable and current data is known as Evidence-Based Practice (EBP). Objective: To assess the organizational and individual barriers to implementing Evidence-based practice among registered nurses in a tertiary care hospital in Mirpur, Azad Kashmir. Methods: A descriptive cross-sectional study was conducted from December 2023 to July 2024 at a tertiary care hospital in Mirpur, Azad Kashmir. Data were collected from 120 registered nurses from different departments with more than one year of clinical experience. The sample size was determined using the Yamane formula. Before starting the data collection process, the study protocol was approved by the Institutional Review Board, and written informed consent was obtained before data collection. A validated questionnaire comprises 24 statements on a five-point Likert scale from strongly disagree to strongly agree was used. Results: The most significant organizational barriers are lack of financial encouragement for using evidence-based practice (M = 4.41), inadequate resources at the workplace (M = 4.25), limited access to updated nursing journals (M = 4.39), and lack of human resources to implement EBP (M = 4.24). Resistance to adopting new strategies (M = 4.22) and limited autonomy in modifying procedures (M = 4.15) are the most common individual barriers. Conclusions: The study highlighted the prevalence of practical barriers that prevent nurses from implementing evidence-based practice and emphasizes the need for healthcare organizations to address them.